Early childhood development : a multicultural perspective - Trawick-Smith, Jeffrey W. (Upper Saddle River, N.J. : Merrill, 2000)
Young children in multicultural perspective. Prenatal development, childbirth, and infancy. Development in the preschool years. The primary years in cultural context. Families in cultural context.
Keywords: Education; Child development; Child development; Multicultural education; Early childhood education; Cognition in children; Observation (Educational method); Handicapped children -- Education